Bioluminescent imaging of Trypanosoma brucei shows preferential testis dissemination which may hamper drug efficacy in sleeping sickness. - Filip Claes; Suman K Vodnala; Nick van Reet; Nathalie Boucher; Hilda Lunden-Miguel; Theo Baltz; Bruno Maria Goddeeris; Philippe Büscher; Martin E Rottenberg (Public Library of Science (PLoS), 2009)
Monitoring Trypanosoma spread using real-time imaging in vivo provides a fast method to evaluate parasite distribution especially in immunoprivileged locations. Here, we generated monomorphic and pleomorphic recombinant Trypanosoma brucei expressing the Renilla luciferase. In vitro luciferase activity measurements confirmed the uptake of the coelenterazine substrate by live parasites and light emission. We further validated the use of Renilla luciferase-tagged trypanosomes for real-time bioluminescent in vivo analysis. Interestingly, a preferential testis tropism was observed with both the monomorphic and pleomorphic recombinants. This is of importance when considering trypanocidal drug development, since parasites might be protected from many drugs by the blood-testis barrier. This hypothesis was supported by our final study of the efficacy of treatment with trypanocidal drugs in T. brucei-infected mice. We showed that parasites located in the testis, as compared to those located in the abdominal cavity, were not readily cleared by the drugs.